Pengaruh Transparansi Dan Akuntabilitas Terhadap Pengelolaan Bantuan Langsung Tunai Dana Desa (BLT-DD) Menurut Perspektif Ekonomi Islam - Putri, Arzika; Farma, Junia (Journal of Economics, Bussiness and Management Issues, 2024)
The Village Fund Direct Cash Assistance Program (BLT-DD) is one of the government's efforts to overcome poverty in the regions, especially in villages. However, the implementation of this program is often faced with various challenges, including the problem of transparency and accountability in fund management. This study aims to determine the effect of transparency and accountability on the management of village fund direct cash assistance from an Islamic economic perspective in Nisam District, Aceh Utara Regency. The research method applied is a quantitative method using multiple regression analysis. The respondents in this study were village officials in Nisam District totaling 80 people. The results of the study indicate that the transparency variable has a positive and significant effect on the management of BLT-DD partially. Likewise, the accountability variable partially shows a positive and significant effect on the management of BLT-DD. In addition, transparency and accountability simultaneously have a positive and significant effect on the management of BLT-DD, with a Determination Coefficient (R²) value of 38. This study is expected to be a reference for policy makers in improving village fund governance effectively and efficiently. In addition, this study can help village officials understand the importance of transparency and accountability in increasing public trust in government programs. Therefore, stricter training and supervision is needed for village officials in terms of financial management based on Islamic principles.